2015
DOI: 10.1088/2041-8205/806/1/l6
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly Evolving and Luminous Transients Driven by Newly Born Neutron Stars

Abstract: We provide a general analysis onthe properties of the emitting material of some rapidly evolving and luminous transients discovered recently with the Pan-STARRS1 Medium Deep Survey. It was found that these transients are probably produced by a low-mass non-relativistic outflow that is continuously powered by a newly born, rapidly spinning, and highly magnetized neutron star (NS). Such a system could originate from an accretion-induced collapse of a white dwarf or a merger of an NS-NS binary. Therefore, observ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 42 publications
(71 reference statements)
3
57
0
Order By: Relevance
“…Fairly speaking, it is not very surprising to find a long-lasting energy engine from an FOT, since such an engine has been widely used to explain some extreme transient phenomena (see Yu et al (2019a) for a brief review), such as superluminous SNe (Woosley 2010; Dexter & Kasen 2013) and gamma-ray bursts Dai 2004;Dai et al 2006;Yu et al 2010). Just following this knowledge, it has been previously suggested by Yu et al (2015) that, at least, the FOTs of an ultrahigh luminosity are very likely to be powered by a central engine, where the luminosity is too high to be explained by the radioactive scenario even though all of the explosivelyejected material is supposed to be radioactive. Generally, the nature of the central engine of an FOT could be a spinning-down neutron star (NS) or a fallback accretion onto a compact object, which can evolve from different progenitors.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Fairly speaking, it is not very surprising to find a long-lasting energy engine from an FOT, since such an engine has been widely used to explain some extreme transient phenomena (see Yu et al (2019a) for a brief review), such as superluminous SNe (Woosley 2010; Dexter & Kasen 2013) and gamma-ray bursts Dai 2004;Dai et al 2006;Yu et al 2010). Just following this knowledge, it has been previously suggested by Yu et al (2015) that, at least, the FOTs of an ultrahigh luminosity are very likely to be powered by a central engine, where the luminosity is too high to be explained by the radioactive scenario even though all of the explosivelyejected material is supposed to be radioactive. Generally, the nature of the central engine of an FOT could be a spinning-down neutron star (NS) or a fallback accretion onto a compact object, which can evolve from different progenitors.…”
Section: Introductionmentioning
confidence: 82%
“…In principle, such a rapid evolution can appear in some ultra-stripped SNe (Tauris et al 2013) or in the shock breakout emission of some normal or failed SNe, which are however disfavored by the un-association of SN 2019bkc with a host galaxy. Therefore, following the considerations in Yu et al (2015) and Yu et al (2018), here we would like to connect SN 2019bkc with a compact object progenitor and model its temporal evolution with a central engine. It is expected that an implication for the origin of SN 2019bkc could be found from the properties of the engine and the explosion ejecta.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 7 shows that these two timescales are well correlated with each other with a ratio around t dec /t rise ∼ (3 − 4). Following Yu et al (2015), the typical value of this ratio can be calculated by (1/ √ 0.1 − 1)/(1 − √ 0.1) = 3.2, by considering of the simplest form of light curves in the magnetar engine model, i.e., L sn ∝ t 2 for t < t peak and L sn ∝ t −2 for t > t peak , where t peak is the peak time. A similar result had been presented in Nicholl et al (2015a), where this t rise − t dec correlation was suggested to be an evidence for the magnetar engine model.…”
Section: Shapes Of Slsn Light Curvesmentioning
confidence: 99%
“…The magnetic field of magnetars is about G, which is about 100-1000 times greater than that of the ordinary pulsar formed in the supernova explosion. Magnetars are thought to be formed by the core-collapse of the highly magnetized massive stars [27][28] or by the NS-NS mergers [29][30] or probably by the accretion induced collapse (AIC) of WD and binary WD merger [31][32]. In our Galaxy, 11 out of 32 massive stars sample show magnetic fields of 1000-5000 G [33], which would be able to result in a strong magnetic field of the final collapsar product for the magnetic flux conservation.…”
Section: Introductionmentioning
confidence: 95%